THE ROLE OF FATHER INVOLVEMENT IN SOCIAL ADJUSTMENT OF FEMALE ADOLESCENTS - Erna Risnawati; Hanifah Alriyanti; Khoiriyah Shoffiyah Tanjung (Universitas Mercu Buana Jakarta, 2023)
Previous research has shown that this process of social adaptation is related to the process of parenting and its relationship with parents. In parenting, of course, there is not only the role of the mother but there is the role of the father who participates in the parenting process. This study aims to determine the role of father involvement in teen girls' adjustment. The study used quantitative methods with purposive sampling technique methods. The participants were 145 female adolescents, aged 12-15 years, who had fathers living together. The instruments used in this study are the scale of social adjustment compiled from the theory of Schneiders and the scale of Father involvement, from Risnawati, Fihadinata, and Wardhni. Data analysis using simple regression. The results showed that there was a relationship between Father Involvement and Social Adjustment in teen girls with R = 0.240, p (0.000) <(0.05), which showed that father involvement played a role of 24% in the social adjustment of teen girls. This research presents a new paradigm that fathers have a significant role in the social development of adolescents, especially teen girls.